Widespread Granuloma Annulare - Jaswal R; Mittal R; Kanwar A J (Wolters Kluwer Medknow Publications, 1999)
A widespread granuloma annulare in a 42 year old female is reported. The lesions were large and annular with sharply defined raised beaded margins and involved the trunk and upper extremities.